Pollen‐derived adenosine is a necessary cofactor for ragweed allergy. Issue 8 (28th May 2015) - Wimmer, M.; Alessandrini, F.; Gilles, S.; Frank, U.; Oeder, S.; Hauser, M.; Ring, J.; Ferreira, F.; Ernst, D.; Winkler, J. B.; Schmitt‐Kopplin, P.; Ohnmacht, C.; et al.
Abstract Background Ragweed (Ambrosia artemisiifolia) is a strong elicitor of allergic airway inflammation with worldwide increasing prevalence. Various components of ragweed pollen are thought to play a role in the development of allergic responses. The aim of this study was to identify critical factors for allergenicity of ragweed pollen in a physiological model of allergic airway inflammation. Methods Aqueous ragweed pollen extract, the low molecular weight fraction or the major allergen Amb a 1 was instilled intranasally on 1–11 consecutive days, and allergic airway inflammation was evaluated by bronchoalveolar lavage, lung histology, serology, gene expression in lung tissue, and measurement of lung function. Pollen‐derived adenosine was removed from the extract enzymatically to analyze its role in ragweed‐induced allergy. Migration of human neutrophils and eosinophils toward supernatants of ragweed‐stimulated bronchial epithelial cells was analyzed. Results Instillation of ragweed pollen extract, but not of the major allergen or the low molecular weight fraction, induced specific IgG1, pulmonary infiltration with inflammatory cells, a Th2‐associated cytokine signature in pulmonary tissue, and impaired lung function. Adenosine aggravated ragweed‐induced allergic lung inflammation. In vitro, human neutrophils and eosinophils migrated toward supernatants of bronchial epithelial cells stimulated with ragweed extract only if adenosine was present. Conclusions Pollen‐derived adenosine is a critical factor in ragweed‐pollen‐induced allergic airway inflammation. Future studies aim at therapeutic strategies to control these allergen‐independent pathways.